(untitled) (International Journal of Engineering and Computer Science, 2015)
In this research a dual system capture method is applied in the development of a biometric fingerprint scanner with enhanced sensitivity and resolution. The device utilizes a combination of the optical imaging and capacitive imaging to capture the biometric features of the fingerprint. The system therefore shuffles between the optical mode and capacitive mode while scanning. Designed software compares and matches the fingerprint using Fourier series. By capturing and matching the minutia features and fingerprint patterns, this scanner can be used for cryptography to authenticate a user.